No spiritual investment in the world gnosticism and postwar German philosophy - Styfhals, Willem 1988- (Ithaca London Cornell University Press and Cornell University Library, 2019)
Crisis : gnostic dualism in late modernity -- Eschaton : gnostic evil in history -- Subversion : heresy and its modern afterlives -- Nothingness : dialectics of religious nihilism -- Epoch : the gnostic age -- Theodicy : overcoming gnosticism, embracing the world
"This book presents an intellectual history of Gnosticism in postwar German philosophy: Jacob Taubes, Hans Blumenberg, Eric Voegelin, Hans Jonas, Gershom Scholem, and Odo Marquard and their interpretations of the relation between Gnosticism and modernity. Recognizing Gnosticism's world-negation in modernity's rejection of spiritual meaning, they claimed to have 'no spiritual investment in the world as it is'"--
Archivierung/Langzeitarchivierung gewährleistet